Dampak dan Efektivitas Program Bantuan Sosial dalam Mengurangi Tingkat Kemiskinan di Indonesia - Pangera, Andi Muh. Fadhal Hiqh. T.; Kamaruddin, Syamsu A; Awaru, A. Octamaya Tenri (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to analyze the impact, effectiveness, and implementation of social assistance programs in Indonesia. This study uses a descriptive qualitative approach with a literature review method. Data was collected through the search of scientific articles indexed in SINTA and Google Scholar. Data analysis techniques were conducted using content analysis, which involves a deep analysis of the contents of documents and articles to identify patterns, trends, and findings relevant to the focus of the research. The research results show that social assistance has a positive impact in alleviating economic burdens and meeting the basic needs of the community, but it still causes social jealousy and dependency. The effectiveness of the program is considered to be suboptimal due to insufficiently accurate data collection. From the implementation side, the main challenges include distribution, transparency, and coordination. Comprehensive improvements are needed so that social assistance is more targeted and sustainable.